The pre-Pleistocene fossil thylacinids (Dasyuromorphia: Thylacinidae) and the evolutionary context of the modern thylacine - Rovinsky,Douglass S.; Evans,Alistair R.; Adams,Justin W. (PeerJ, 2019)
The thylacine is popularly used as a classic example of convergent evolution between placental and marsupial mammals. Despite having a fossil history spanning over 20 million years and known since the 1960s, the thylacine is often presented in both scientific literature and popular culture as an evolutionary singleton unique in its morphological and ecological adaptations within the Australian ecosystem. Here, we synthesise and critically evaluate the current state of published knowledge regarding the known fossil record of Thylacinidae prior to the appearance of the modern species. We also present phylogenetic analyses and body mass estimates of the thylacinids to reveal trends in the evolution of hypercarnivory and ecological shifts within the family. We find support that Mutpuracinus archibaldi occupies an uncertain position outside of Thylacinidae, and consider Nimbacinus richi to likely be synonymous with N. dicksoni. The Thylacinidae were small-bodied (< ~8 kg) unspecialised faunivores until after the ~15–14 Ma middle Miocene climatic transition (MMCT). After the MMCT they dramatically increase in size and develop adaptations to a hypercarnivorous diet, potentially in response to the aridification of the Australian environment and the concomitant radiation of dasyurids. This fossil history of the thylacinids provides a foundation for understanding the ecology of the modern thylacine. It provides a framework for future studies of the evolution of hypercarnivory, cursoriality, morphological and ecological disparity, and convergence within mammalian carnivores.
Keywords: Tasmanian tiger; Thylacinus cynocephalus; Marsupial; Hypercarnivory; Body mass; Parsimony; Phylogeny; Middle Miocene climatic transition